CONDITION AND PROBLEMS OF DEVELOPMENT OF LAND RECLAMATION IN DAGESTAN - A. M. Zеrbаliev (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
In the article the modern condition of drainage systems and irrigated land in Dagestan and tasks to improve the technical condition of irrigation systems for the rational use of irrigation water and increase the productivity of reclaimed lands.